1stFlip Flipbook Creator-Assisted E-Module to Advance Learning Quality in Elementary Schools - Maulidya, Syifa Andriana; Zulherman (Universitas Pendidikan Ganesha, 2024)
The current emphasis is on enhancing fourth graders' IPAS learning through the use of engaging learning materials, as there has been little innovation in this area. Using cutting-edge interactive media, this study intends to develop an E-module using 1stflip Flipbook in order to raise students' engagement, performance, and the overall quality of their education. The R&D approach, namely the ADDIE model, is utilized for the research. Experts in media, materials, and languages validated the research instruments. Validators filled out questionnaires, and students took pretests and post-tests; data was gathered through interviews and observations. The data was analyzed using quantitative and descriptive methods. The results of the validation showed that the E-module was valid at 78.3%, with an N-Gain value of 63.16% for the experimental class and 29.39% for the control class. The results of the hypothesis test demonstrated that the group of students who used the E-module significantly outperformed the control group in terms of their metacognitive skill improvement. There is significant value in enhancing the quality of learning through the usage of E-Modules with 1stflip Flipbook to enhance IPAS learning in primary schools.